The adjuvant treatment role of ω-3 fatty acids by regulating gut microbiota positively in the acne vulgaris - Yaxin Huang; Fuming Liu; Jindong Lai; Shiyu Jiang; Xiaoqi Tan; Lingna Chen; Yong Xu; Xia Xiong; Yongqiong Deng (Taylor & Francis Group, 2024)
AbstractObjectives:We aimed to explore the potential role of omega-3 (ω-3) fatty acids on acne vulgaris by modulating gut microbiota.Materials and Methods:We randomly divided the untreated acne patients into two groups with or without ω-3 fatty acids intervention for 12 weeks. The Sprague Dawley (SD) rats with acne model were given isotretinoin, ω-3 fatty acids or their combination respectively. Then the colonic contents samples of the drug intervention SD rats were transferred to the pseudo sterile rats with acne model. The severity of the disease was assessed by the Global Acne Grading System (GAGS) score of the patients, and the swelling rate of auricle and the pathological section of the rat with acne model. The 16S rDNA gene sequencing was performed to detect the alteration of the gut microbiota.Results:ω-3 fatty acids could increase the diversity of the gut microbiota and regulate the flora structure positively both in the patients and rats, increase the abundance of butyric acid producing bacteria and GAGS score in the patients, and alleviate the inflammation and comedones of rats.Conclusion:Supplementation of ω-3 fatty acids could alleviate the inflammation of acne vulgaris by increasing the abundance of butyric acid producing bacteria.